Sensitive Fibre-Based Thermoluminescence Detectors for High Resolution In-Vivo Dosimetry - Ghomeishi, Mostafa (Sci Rep, 2015)
With interest in the potential of optical fibres as the basis of next-generation thermoluminescence dosimeters (TLDs), the development of suitable forms of material and their fabrication has become a fast-growing endeavour. Present study focuses on three types of Ge-doped optical fibres with different structural arrangements and/or shapes, namely conventional cylindrical fibre, capillary fibre, and flat fibre, all fabricated using the same optical fibre preform. For doses from 0.5 to 8 Gy, obtained at electron and photon energies, standard thermoluminescence (TL) characteristics of the optical fibres have been the subject of detailed investigation. The results show that in collapsing the capillary fibre into a flat shape, the TL yield is increased by a factor of 5.5, the yield being also some 3.2 times greater than that of the conventional cylindrical fibre fabricated from the same perform. This suggests a means of production of suitably sensitive TLD for in-vivo dosimeter applications. Addressing the associated defects generating luminescence from each of the optical fibres, the study encompasses analysis of the TL glow curves, with computerized glow curve deconvolution (CGCD) and 2(nd) order kinetics.